Sleep disorders in university students during COVID-19: United States of America, Mexico and El Salvador - Chacon Andrade, Edgardo Rene; Lobos Rivera, Marlon Elias; Flores Monterrosa, Angelica Nohemy; Perez, Miguel A; Durón, Maria Fernanda (Horizonte Sanitario, 2022)
Objective: The purpose of this cross-sectional study was to measure students’ sleep disorders 12 months after the start of the COVID-19 pandemic. Materials and Methods: Data were collected from 693 students from three universities in El Salvador, Mexico, and the United States using the Student Health Behavior Inventory. Results: Sleep disorders were identified in the sample with those in the US reporting higher levels of sleep disorders and those in El Salvador reported the least. Differences were also observed by gender with females reporting more sleep disorders one year into the pandemic than males. Conclusions: The global pandemic related to COVID-19 has had a profound impact on the mental and physical wellbeing of students. Sudden changes in learning modalities, modifications to work schedules, and potential loss of loved ones have contributed to sleep disorders in this population group. Universities need to take steps to address the evolving needs of college students as they cope with this pandemic. Keywords: Sleep; Coronavirus; Students; Cross-cultural comparison